Exploring the drivers of Spain's nutritional transition: From meat shortages to excess (1958-1990) - Pablo Delgado (European Historical Economics Society (EHES), 2023)
The modern nutritional transition is characterized by a significant increase in protein consumption derived from animal-based foods, particularly meat. Despite its importance, the underlying drivers of this process have not been extensively explored, especially from a quantitative perspective. Some authors attribute it to demand-side factors such as growth in income, population, and urbanization rates, while others focus on supply-side factors such as the decline in livestock product prices due to the intensification of the livestock industry. This study seeks to fill this gap by examining quantitatively the role of demand, supply, and consumer preferences in driving the increase in meat consumption in Spain, a Mediterranean country that completed its modern nutritional transition in the latter half of the 20th century.
Keywords: N34; N54; O13; E21; 330; nutritional transition; meat; Spain; consumption